PsycEXTRA Dataset 2006
DOI: 10.1037/e609222007-001
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health Characteristics of U.S. and Foreign-Born Adults: United States, 1998-2003

Abstract: Objective-This report presents national prevalence estimates of selected measures of physical health status and limitations, health care access and utilization, and mental health status among the civilian noninstitutionalized population of U.S. and foreign-born adults aged 18 years and over in four race-ethnicity groups in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 15 publications
9
138
4
5
Order By: Relevance
“…Past research has found that foreign-born Latino men are more likely to smoke compared to their female compatriots and that, viewed collectively, a smaller percent of all foreign-born Latino adults smoke compared to all US-born adults and to other US-born minority groups separately (except for Asians). [24][25][26] These results should be interpreted with some caution, however, given that Latino immigrants are also more likely to underreport smoking behavior. 27 And, it is important to note when considering factors influencing Latino immigrant smoking, especially "acculturation," which has often been viewed simply as an individual-level adjustment process, that the tobacco industry has developed strategies to market directly to foreign-born Latin American populations in the USA.…”
Section: Introductionmentioning
confidence: 90%
“…Past research has found that foreign-born Latino men are more likely to smoke compared to their female compatriots and that, viewed collectively, a smaller percent of all foreign-born Latino adults smoke compared to all US-born adults and to other US-born minority groups separately (except for Asians). [24][25][26] These results should be interpreted with some caution, however, given that Latino immigrants are also more likely to underreport smoking behavior. 27 And, it is important to note when considering factors influencing Latino immigrant smoking, especially "acculturation," which has often been viewed simply as an individual-level adjustment process, that the tobacco industry has developed strategies to market directly to foreign-born Latin American populations in the USA.…”
Section: Introductionmentioning
confidence: 90%
“…The NHIS has been used to examine health care issues regarding both Hispanic subgroups as well as people who are foreign born and living in the United States. 15,20 …”
Section: Designmentioning
confidence: 99%
“…Al respecto, se han realizado estudios que muestran que la autopercepción de salud general y salud mental de este grupo sería de regular a mala 4,5 . Además, se ha evidenciado que la salud mental en los inmigrantes puede estar afectada negativamente por el mismo proceso migratorio 6,7 .…”
unclassified
“…Además, se ha evidenciado que la salud mental en los inmigrantes puede estar afectada negativamente por el mismo proceso migratorio 6,7 . Estudios realizados en Estados Unidos de Norteamérica, han reportado que la tasa de trastornos psiquiátricos de la población inmigrante es menor en comparación a los sujetos nacidos en ese país 4,8 . En Europa, las cifras encontradas son variadas.…”
unclassified